Survey of Dermatophytes in Stray Cats with and without Skin Lesions in Northern Italy. (13th May 2014) - Proverbio, Daniela; Perego, Roberta; Spada, Eva; Bagnagatti de Giorgi, Giada; Della Pepa, Alessandra; Ferro, Elisabetta
Abstract : The aim of this study was to determine the prevalence of dermatophytes in stray cats with and without clinical lesions from different colonies in rural and urban areas of Milan and surroundings in northern Italy. Stray cats (273) were caught during a trap-neuter-release (TNR) program conducted in different colonies of northern Italy in both rural and urban areas. Each cat was examined in dark environment with a Wood's lamp prior to sample collection. Hair or scales exhibiting typical fluorescence were removed with a pair of sterile hemostats and cultured. The hair of all cats was then sampled by Mackenzie modified brush technique regardless of the presence or absence of skin lesions attributable to dermatophytosis. All the hair samples were subjected to fungal culture. 15 cats were positive (5.5%). Microsporum canis was the most common dermatophyte isolated (13/15). The only other isolated dermatophyte was Trichophyton mentagrophytes (2/15). Our estimated prevalence of dermatophytes in stray cats was much lower than other Italian studies on the same population.